Challenges posed by novel vaccines in a hyperlinked society both to doctors and the health of their patients - Ihan, Alojz (Medicine, Law & Society, 2018)
Medicine in the developed world is becoming progressively more commercialized since patients (or, more accurately, medical consumers) are increasingly becoming the driving force of what we call medical progress. The doctors are primarily obliged to treat and help patients, but will always have also (commercial) temptation before him: to facilitate the consumer's desires and, with a warm heart, shoot to the far borders of medical knowledge and technology. A good example illustrating dilemma of beneficial vs commercial medicine are ethical challenges of some new vaccines developed recently. Since their earliest introduction in the late 18th century, vaccines have undoubtedly saved the lives of millions, while also fundamentally changing the way modern medicine is practiced. Many diseases that were once widespread are now eradicated, yet vaccine development faces ongoing challenges, including some important ethical considerations. Today there are over 300 vaccines in development and included in clinical trials. Among them, anti-addiction vaccines (Cocaine, Nicotine, Fentanyl, Heroin, Oxycodone) received a burst of media attention, because these vaccines could help people in recovery from addiction; however, many ethical and legal questions may arise before clinical use.
Keywords: Conflicts of interest; physicians; commercialization; populism; public health; vaccine development; anti-addiction vaccines; vaccines for pregnant mothers; ethical and legal questions